The Effectiveness of Percutaneous Balloon Compression, Thermocoagulation, and Glycerol Rhizolysis for Trigeminal Neuralgia in Multiple Sclerosis. Issue 4 (October 2019) - Noorani, Imran; Lodge, Amanda; Vajramani, Girish; Sparrow, Owen
Abstract : BACKGROUND : Balloon compression (BC), thermocoagulation (TC), and glycerol rhizolysis (GR) are percutaneous surgical options for trigeminal neuralgia (TN). Whether the outcomes of these procedures in multiple sclerosis ‐related TN (MS‐TN) are as effective as in idiopathic TN (ITN) is unknown. OBJECTIVE : To retrospectively compare pain relief, complications, and durability achieved by these 3 types of procedures in MS‐TN and ITN. METHODS : Two hundred and four patients with typical TN were treated percutaneously: 33 had MS‐TN (64 procedures) and 171 had ITN (329 procedures). All were performed by 1 of 2 neurosurgeons; interviews enabled long‐term data to be gathered by an independent observer. RESULTS : MS‐TN patients (53.1%) had Barrow Neurological Institute pain scores of I or II after a percutaneous procedure, compared with 59.3% in the ITN cohort; there was no difference in initial relief between the 2 groups overall ( P = .52). There was a trend toward fewer complications in MS‐TN compared with ITN (23.4% vs 33.7%, respectively; P = .058). Kaplan‐Meier analysis demonstrated no difference in durability of relief in MS‐TN (median 23.0 mo) compared with ITN overall (median 24.0 mo; P = .75). Subgroup analysis demonstrated longer relief from BC and TC compared with GR in MS‐TN ( P = .013). Multivariate analysis confirmed that although the presence of MS does not predict durability of outcome, postoperative numbness ( P = .0046) and undergoing a repeat procedure ( P = .037) were significant predictors. CONCLUSION : BC and TC are safe and effective in MS‐TN. Postoperative numbness is the strongest prognostic factor in MS‐TN.